LA SUPERFICIE SLA STRAUMANN DEL IMPLANTE ITI. - Sueldo, Efraín (1998)
ITI dental implants have used a titanium plasma-sprayed surface since the first ITI implant was inserted in 1974. Research on surface treatments for titanium identified a SAND-BLASTED LARGE GRIT A CIDETCHET surface for anchoring dental implants in bone. The propierties of the surface were compared with the titanium plasmasprayed and other surfaces uses on dental implants in a series of in vitro and in vivo tests. The SLA surface, patented by Straumann, performed well in cell cultures, in bone histology, and removal torque tests in animals. The advantages in any one test over the titanium plasmasprayed surface were slight, but the whole set of results taken together suggest that the SLA surface may osseointegrate faster and could further improve the perfonmance of the ITI dental implants. First results from clinical trials with a healing time 6-8 weeks before restoration indicate that these shortened healing times will became standard treatment in the future.